Acoustic scattering of broadband echolocation signals from prey of Blainville's beaked whales : modeling and analysis - Jones, Benjamin A. (Benjamin Aaron) (Massachusetts Institute of Technology, 2006)
Thesis (S.M.)--Joint Program in Oceanography/Applied Ocean Science and Engineering (Massachusetts Institute of Technology, Dept. of Mechanical Engineering; and the Woods Hole Oceanographic Institution), 2006. This electronic version was submitted by the student author. The certified thesis is available in the Institute Archives and Special Collections. Includes bibliographical references (p. 89-96). Blainville's beaked whales (Mesoplodon densirostris) use broadband, ultrasonic echolocation signals (27 to 57 kHz) to search for, localize, and approach prey that generally consist of mid-water and deep-water fishes and squid. Although it is well known that the spectral characteristics of broadband echoes from marine organisms are a strong function of size, shape, orientation and anatomical group, little is known as to whether or not these or other toothed whales use spectral cues in discriminating between prey and non-prey. In order to study the prey-classification process, a stereo acoustic tag was mounted on a Blainville's beaked whale so that emitted clicks and corresponding echoes from prey could be recorded. A comparison of echoes from prey selected by the whale and those from randomly chosen scatterers suggests that the whale may have, indeed, discriminated between echoes using spectral features and target strengths. Specifically, the whale appears to have favored prey with one or more deep nulls in the echo spectra as well as ones with higher target strength. A three-dimensional, acoustic scattering model is also developed to simulate broadband scattering from squid, a likely prey of the beaked whale. (cont.) This model applies the distorted wave Born approximation (DWBA) to a weakly-scattering, inhomogeneous body using a combined ray trace and volume integration approach. Scatterer features are represented with volume elements that are small (less than 1=12th of the wavelength) for the frequency range of interest (0 to 120 kHz). Ranges of validity with respect to material properties and numerical ...